A STUDENT MOTIVATION AND HIS IN EDUCATION ROLE - Utkir Kurbonovich, Utanov; Abdurashid Omonkulovich, G‘ulomov (Journal of Higher Education and Academic Advancement, 2024)
Objective: This study aims to analyze the role of student motivation in Uzbekistan's education system, exploring various types of motivation (internal, external, term-based, and permanent) and their impact on students' academic performance, personal development, and future career aspirations. Methods: The research employs a qualitative approach, utilizing surveys and interviews with students, teachers, and education administrators to gather insights into motivational factors and their effects on the educational process. Results: Motivated students demonstrate high academic achievement, active participation in educational activities, and significant personal growth. These students set clear goals, manage their time effectively, and engage in creative and social activities that enhance their skills. Motivated students are also more confident and prepared for future professional challenges. Novelty: This study highlights the importance of tailored teaching methods, such as interactive lessons, rewards, and personalized approaches, in boosting student motivation. It emphasizes the need for educators to foster both intrinsic and extrinsic motivation to ensure long-term educational success and prepare students for a knowledge-based economy.